Syntheses and magnetic properties of a series of discrete Ni(II)-Ln(III) heterometallic complexes based on 2, 3-dichlorobenzoate and 2, 2′-bipyridine. (15th September 2021) - Zheng, Jia-Hui; Zhang, Yu-Han; Shen, Yue; Chen, Fei-Yue; Liu, Bin-Qiu; Zhang, Ju-Wen
Graphical abstract: Eight isostructural linear tetranuclear heterometallic clusters have been successfully synthesized and structurally characterized. Their magnetic properties have been investigated. Abstract: Herein, a series of zero-dimensional (0D) heterometallic complexes, [Ln2 Ni2 (2, 3-DCB)10 (2, 2′-bpy)2 ] [Ln = Nd (1 ), Sm (2 ), Eu (3 ), Gd (4 ), Tb (5 ), Dy (6 ), Er (7 ) and Yb (8 )], were obtained by the reactions of Ln(NO3 )3 · n H2 O, Ni(NO3 )2 ·6H2 O, 2, 3-dichlorobenzoic acid (2, 3-HDCB), NaOH and 2, 2′-bipyridine (2, 2′-bpy) under solvothermal conditions. The structures of complexes 1 –8 were determined by single-crystal X-ray diffraction and further characterized by elemental analysis, FT-IR, PXRD and TGA. Complexes 1 –8 are isostructural, and display discrete linear tetranuclear cluster structures constructed from ten 2, 3-DCB anions linking two Ln(III) and two Ni(II) ions by four types of coordination modes. Such linear tetranuclear molecules can be extended into a two-dimensional (2D) supramolecular network through π–π interactions between 2, 3-DCB and 2, 2′-bpy. The magnetic properties of complexes 1 –8 were also studied.